VD_FINDINFO AF 5/09 - 4/2011 vom 7. Juli 2011 - VD Tribunal cantonal (2011)
LOI FÉDÉRALE SUR LES ALLOCATIONS FAMILIALES, DEMANDE ADRESSÉE À L'AUTORITÉ, PRESCRIPTION | 10 al. 5 LAlloc, 56 al. 1 LPGA, 60 al. 1 LPGA, 61 let. a LPGA, 61 let. b LPGA, 61 let. g LPGA, 2 al. 1 let. c LPA-VD, 79 LPA-VD, 94 al. 1 let. a LPA-VD